The Legal Limits of Direct Democracy A Comparative Analysis of Referendums and Initiatives across Europe - Moeckli, Daniel; Forgács, Anna; Ibi, Henri (Edward Elgar Publishing, 2021)
With the rise of direct-democratic instruments, the relationship between popular sovereignty and the rule of law is set to become one of the defining political issues of our time. This important and timely book provides an in-depth analysis of the limits imposed on referendums and citizens' initiatives, as well as of systems of reviewing compliance with these limits, in 11 European states.